Response to Jetter and Swasito (2024) - Daniel Mattingly (Institute for Replication (I4R), 2024)
Rigorous replication efforts is crucial for good social science, and I am grateful to Jetter and Swasito (2024), who replicate and extend the results of a recent published paper (Mattingly, 2024). My original paper examined, among other things, the ways in which periods of foreign and domestic threat shaped how the Chinese Communist Party selected officers for the People's Liberation Army (PLA). Jetter and Swasito confirm the core results are computationally replicable. To extend the results, they use alternative data sources to measure foreign and domestic threat. They conclude that the domestic threat results in particular are not robust to the alternative data source they use. I raise questions about the quality of this alternative data source. I also ask whether, even if the data were of higher quality, it would map onto the core concept. Finally, I argue for the importance of substantive knowledge of the case and qualitative scoring of the foreign and domestic threat variable. However, the points raised by Jetter and Swasito in their replication effort are important and well-taken. Measuring concepts such as foreign and domestic threat is challenging, and doing so is a potential avenue for future quantitative research.
Keywords: 330